(untitled) (Journal of the College of Basic Education, 2025)
Urban geography, as a branch of human geography, is concerned with studying urban areas or what is related to them in terms of influence and being influenced. That is, the city represents the applied field of geography in a spatial context. Since the urban environment represents the most changing of geographical environments, it is considered a tangible model of what humans have done to their geographical environment in terms of construction, development, and change. Thus, the city is truly an environment created by humans for themselves and by themselves (Ghallab, 1975). The beginnings of the study of urban geography date back to the first third of the twentieth century when Cristhaler wrote his theory of "Central Places" in 1934, which was considered a methodological breakthrough in his approach to the phenomenon of the city in terms of its complete understanding of its concept, and the information collected about it formed the scientific foundations for the study of urban geography (Al-Abadi, 1975). (1974) The concept of development has become more expansive, as it includes, in addition to economic development, social development, so that the development process extends to other aspects after it was for a considerable period limited to economic aspects only (Al-Amin, 2006). Development is defined as a process of change in the economic and social structure, and in various aspects of activity, and manifestations of social and economic behavior, a change that extends to multiple aspects of the life of society in construction and movement, including all aspects of social, economic and cultural life quantitatively and qualitatively (Hamad, 2008). The city of Al-Hasahisa is a meeting point for the road network that connects the different regions of Sudan and is surrounded by a large group of villages. In general, cities depend on the surrounding countryside and are strongly linked to it in the form of economic, social and service relations (Al-Abadi, 1974(